Determination of mass-dependent variations in tungsten stable isotope compositions of geological reference materials by double-spike and MC-ICPMS - Abraham, K; Barling, J; Siebert, C; Belshaw, N; Gall, L; Halliday, A (Royal Society of Chemistry, 2015)
We present a double-spike technique for precise determination of mass-dependent fractionation of tungsten (W) stable isotopes. Instrumental mass bias effects and isotope fractionation during W separation are corrected for by means of a 180W-183W double-spike added prior to sample dissolution. The separation of W from matrix is achieved via three-step anion-exchange chromatography. Tungsten stable isotopic compositions were determined by multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS). Results are expressed relative to the NIST SRM 3136 W standard as the permil difference in 186W/184W (186W). The external reproducibility of the NIST SRM 3163 W standard is ±0.05 ‰ with an average composition of -0.01 ‰ on 186W/184W (2 s.d., n=171). Tungsten stable isotope compositions for USGS standard reference materials are as follows: AGV-2 (andesite;186W=0.18±0.05 ‰, 2s.d., n=6), SDC-1 (mica schist; 186W=0.36±0.05 ‰, 2s.d., n=6), SDO-1 (shale; 186W=0.26±0.06 ‰, 2s.d., n=6), and manganese nodules NOD-A-1 (186W=0.07±0.05 ‰, 2s.d., n=10) and NOD-P-1 (186W=0.31±0.04 ‰, 2s.d., n=7). The long-term external reproducibility (2 s.d.) for these rock standards is ±0.05 ‰.